Ending human trafficking and modern-day slavery: freedom's journey - Enrile, Annalisa V. (SAGE, 2018)
Acknowledgments -- Preface -- Historical contexts, definitions and root causes of human trafficking and modern day slavery -- Introduction and history of human trafficking and modern day slavery -- The law of supply and demand : the business of trafficking -- Social determinants of human trafficking and modern day slavery -- Clinical interventions -- Trauma informed care -- Case management -- Trauma focused cognitive behavior therapy -- Survivor advocate model -- Interventions for commercially sexually exploited children (CSEC) -- Policy interventions -- Landmark policies in trafficking and modern day slavery -- Supply chain transparency -- Advocacy, activism and innovations -- Grassroots? : advocacy and activism -- Faith based organizations -- Prevention -- Social innova -- Glossary -- References